Family education for preventing shyness in preschool children - Sampayo Hernández, Isabel Cristina; Valle de Zayas, Beatriz; Guerrero Fernández, Esmérido (Transformación, 2024)
Objective: The article aims reviewing family education on the prevention of shyness in preschool children.Methods: The authors rely both on theoretical and practical level methods, such as analysis and synthesis, deductive and inductive procedures, documents reviewing, observation, interviewing, and surveying.Result: The study proved the need of improving family orientation in educational practice and made it possible to show that the manifestations of shyness that children present, for the most part, are the result of an inadequate fulfillment of the educational role of the family in the family coexistence.Conclusion: Family counseling should promote awareness of the importance of developing adequate communication with the child in family life and the need of taking advantage of the social interactions to pay attention to the experiences, in order to prevent manifestations of shyness.
Keywords: Family education; family counseling; prevention; shyness; preschool children